Analisis Implementasi Model Discovery Learning terhadap Kemampuan Berpikir Kritis Peserta Didik di SD/MI - Frasandy, Rendy Nugraha; Dewi, Tri Ratna; Septikasari, Resti (Universitas Islam Negeri Imam Bonjol Padang, 2023)
This study aims to analyze how the application of the Discovery Learning Model in improving students' critical thinking skills in thematic learning in SD/MI. The research method used is library research with the type of research, namely qualitative research, which uses journal articles as the main object. The data sources used in this research are 8 (eight) journal articles about the application of the Discovery Learning model in improving students' critical thinking skills in thematic learning in SD/MI. The data analysis technique used in this study is the Content analysis method. The results of the analysis of 8 (eight) journal articles on the application of the Discovery learning model to improve students' critical thinking skills in thematic learning in SD/MI found an increase in students' critical thinking skills in thematic learning in SD/MI after the implementation of the Discovery learning model. This happens because at the time of applying the steps of the Discovery learning model there are indicators of critical thinking skills put forward by Ennis, namely providing simple explanations that occur during problem statement activities, Building basic skills occurs during date collaction activities, giving action occurs during activity date processing, concludes that it occurs during verification activities, and finally, has confidence that occurs during generalization activities. As well as being a reference for learning models for teachers to improve students' critical thinking skills in thematic learning in SD/MI, even more so on the subject matter of natural science and Mathematics besides that the Discovery learning model is highly recommended to be applied in high grade IV (four), because in the application of the Discovery learning model in grade IV (four) get very good results in improving students' critical thinking skills in elementary/MI thematic lessons.